Faktor Risiko Terjadinya Obesitas Pada Remaja SMA - Imelda Telisa; Yuli Hartati; Arif Dwisetyo Haripamilu (Faletehan Health Journal, 2020)
Adolescents with the nutritional status of obesity in Indonesia have increased in number each year. Factors causing obesity in adolescent is multifactorial. Excessive intake of macro-nutrient, increased consumption of fast food, lack of physical activity, genetic factors, psychological factors, the amount of pocket money, the influence of advertising, socioeconomic status, no breakfast, age, and gender are the factors of diet and lifestyle change. They may cause energy imbalance which results on obesity risk. The study aims to determine the factors that influence the risk of obesity in adolescent. This study is analytical observational with cross sectional design. 118 10th and 11th graders were taken as samples by proportional stratified random sampling technique. Statistical analysis showed that the factors significantly associate and become the risk factors are energy intake (p-value 0.000; OR = 2.97); protein (p-value 0.005; OR = 3.49); fat (p-value 0.000; OR = 6.57); carbohydrates (p-value 0.050; OR = 2.00); consumption of fast food (p-value 0.000; OR = 4.41); physical activity (p-value 0.007; OR = 3.08); pocket money (p-value 0.032; OR = 2.38); and genetic (p-value 0.001; OR = 3.98). Adolescents with excessive macro nutrient intake, frequent consumption of fast food, low physical activity, high pocket money and a history of obese parents have a greater occurrence risk of obesity.